The effects of resource appropriation on the behavior of mangrove resource users towards mangrove preservation in Bagong Buswang, Kalibo, Aklan - Uy,William; Daquipil, Rey J. (2009.)
The research described how the appropriation of resources taken from the mangrove affectsw the behavior of resource users. The locale of the research in bakhaw Ecopark, New Buswang, Kalibo, Aklan where rapid urbanization threate3ns to affect the condition of its natural resources. The research subjects are households sorrounding the ecopark, KASAMA, USWAG, the scientific community, and tourists. Uswing survey questionaire and key informant interviews the study examined the differences and similarities in resource utilization and perspectives, and how these may affect the magrove resource. The research found out that the pattern of resource appropriation emerging from both legal and customary rules affected the resource users. Their status as resource user limits their activities with respect to the mangrove resource. The resulting differences in activities due to the restriction on r4esource appropriation led to mangrove resource preservation. The varying activities and interst of the users tend to cater to the other and as a result benefits all of the resource users.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: Magroves preservation -- Bagong Buswang, Kalibo, Aklan -- Research